The Preparation of Banking Industry in Implementing IFRS 9 Financial Instruments (A Case Study of HSBC Holdings Plc Listed on London Stock Exchange of Year 2015–2017) - Johannes, Rene; Dedy, Dedy; Muksin, Abdullah (International Journal of Economics and Financial Issues, 2018)
Global financial crisis 2008 was a very close call of total systemic collapse in financial markets. This had urged the leaders of G20 to involve the key global accounting standards bodies for creating a single high-quality global standard. IFRS 9 ‘Financial Instruments’ released in 2014 is a project of IASB to achieve that goal and its effective date is 1 January 2018. However, a poll found that 46 percent of 91 banks in the world (excluding some U.S. banks) believe not having adequate resources to implement the standard by 2018. That is why this research wants to figure out the preparation of banking industry especially HSBC Holdings Plc to implement the standard. Using an exploratory research method, the researcher has found out that HSBC has been well-prepared to implement the standard. The findings of this research also realize a certain extent of agreement to MacNeal’s theory and positive theory introduced by Watts & Zimmerman. Keywords: IAS 39, IFRS 9, financial instruments, recognition and measurement, financial reporting JEL Classifications: G11, G21, G32 DOI: https://doi.org/10.32479/ijefi.7280